1998
DOI: 10.1515/cclm.1998.027
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Ascorbic Acid Ingestion on the Biochemical and Physicochemical Risk Factors Associated with Calcium Oxalate Kidney Stone Formation

Abstract: The present study was undertaken to determine the effect of ingestion of large doses of vitamin C on urinary oxalate excretion and on a number of other biochemical and physicochemical risk factors associated with calcium oxalate urolithiasis. A further objective was to determine urinary ascorbate excretion and to relate it qualitatively to ingested levels of the vitamin and oxalate excretion. Ten healthy males participated in a protocol in which 4 g ascorbic acid was ingested for 5 days. Urines (24 h) were col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
34
1
8

Year Published

1999
1999
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(43 citation statements)
references
References 16 publications
0
34
1
8
Order By: Relevance
“…Ascorbic acid at 4 g/day was chosen for this study because such a dosage was reported to be safe without increased urinary oxalate (44,45) and a similar dose was found to be effective in a previous clinical study for preventing nephrotoxicity after contrast medium injection (46). In this study, the overall incidence of nephrotoxicity, determined according to the widely used RIFLE criteria (39), was 50 to 60%, and it was not significantly different from that observed in the patients at Siriraj Hospital in 2007 (47).…”
Section: Discussionmentioning
confidence: 99%
“…Ascorbic acid at 4 g/day was chosen for this study because such a dosage was reported to be safe without increased urinary oxalate (44,45) and a similar dose was found to be effective in a previous clinical study for preventing nephrotoxicity after contrast medium injection (46). In this study, the overall incidence of nephrotoxicity, determined according to the widely used RIFLE criteria (39), was 50 to 60%, and it was not significantly different from that observed in the patients at Siriraj Hospital in 2007 (47).…”
Section: Discussionmentioning
confidence: 99%
“…49,50 Despite better assays, controversy remains. 33,[51][52][53][54][55][56] Taken together, the data show that oxalate excretion is probably increased at vitamin C doses of 1 g or more daily in some healthy people, although consequences are unclear. In people with underlying hyperoxaluria, oxalate excretion is accelerated by ascorbate doses of 1 g or more, and for these people megadoses could be harmful.…”
Section: Adverse Effectsmentioning
confidence: 98%
“…Vitamin C in doses up to 4 g per day can be taken without increasing the risk of stone formation [48]. Animal protein should not be ingested in excessive amounts [49, 50].…”
Section: Treatmentmentioning
confidence: 99%